Introduction to multilingualism. Program of classes in the language education (glottodidactics) specialization - Pałuszyńska, Edyta (Papers in Linguistics, 2021)
The article describes a curriculum of a semester-long course in “Introduction to multilingualism”. The text specifies the effects of teaching with respect to knowledge, skills and competences, the main educational content and literature of the course. The goal of the proposed course consists in systematising and passing on to students of language education knowledge related to speech therapy, psycholinguistic, neurobiological and sociological knowledge regarding the development of child speech, including development in multilingual environments and multilingualism in adults. The curriculum of the course encompasses topics concerning types of multilingualism, characteristics of multilingual development of child speech, techniques for supporting speech development in multilingual environments, risks and difficulties in simultaneous multilingualism and multilingualism in adults.